A periplasmic protein modulates the proteolysis of peptidoglycan hydrolases to maintain cell wall homeostasis in Escherichia coli - Sohee Park; Wook-Jong Jeon; Yeseul Lee; Chae Lim Lim; Eunyeong Lee; Han Byeol Oh; Gyu Sung Lee; Oh Hyun Kwon; Bumhan Ryu; Yong-Joon Cho; Chung Sub Kim; Sung-il Yoon; et al. (Proceedings of the National Academy of Sciences, 2025)
Bacterial cell wall assembly and remodeling require activities of peptidoglycan (PG) hydrolases as well as PG synthases. In particular, the activity of DD-endopeptidases, which cleave the 4-3 peptide crosslinks in PG, is essential for PG expansion in gram-negative bacteria. Maintaining optimal levels of DD-endopeptidases is critical for expanding PG without compromising its integrity. In Escherichia coli , the levels of major DD-endopeptidases, MepS and MepH, along with the lytic transglycosylase MltD, are controlled by the periplasmic protease Prc and its outer membrane adaptor NlpI. However, the mechanisms regulating the turnover of these PG hydrolases have remained unclear. In this study, we identified a periplasmic protein, BipP (formerly YhjJ), that negatively controls the NlpI-Prc system. Further analyses indicate that BipP exerts this control by interacting with NlpI and inhibiting its substrate recognition in response to low DD-endopeptidase activity, providing insight into the homeostatic control of PG hydrolysis and cell wall expansion.